2022
DOI: 10.1038/s41523-022-00416-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial interplay of lymphocytes and fibroblasts in estrogen receptor-positive HER2-negative breast cancer

Abstract: In estrogen-receptor-positive, HER2-negative (ER+HER2−) breast cancer, higher levels of tumor infiltrating lymphocytes (TILs) are often associated with a poor prognosis and this phenomenon is still poorly understood. Fibroblasts represent one of the most frequent cells in breast cancer and harbor immunomodulatory capabilities. Here, we evaluate the molecular and clinical impact of the spatial patterns of TILs and fibroblast in ER+HER2− breast cancer. We used a deep neural network to locate and identify tumor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…4A) were not only located in tumor stroma (P < 0.0001), but also in the adjacent normal tissue (P < 0.0001). Moreover, the model was also able to capture complex cell interactions, as spatial mixing of fibroblasts and tumor infiltrating lymphocytes (TILs) were also retrieved in low risk tiles (P = 2.5E-04), a feature of good prognosis highlighted in a recent study (35). These results showed that our model was able to capture well-established prognostic factors as well as complex and novel patterns to predict patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…4A) were not only located in tumor stroma (P < 0.0001), but also in the adjacent normal tissue (P < 0.0001). Moreover, the model was also able to capture complex cell interactions, as spatial mixing of fibroblasts and tumor infiltrating lymphocytes (TILs) were also retrieved in low risk tiles (P = 2.5E-04), a feature of good prognosis highlighted in a recent study (35). These results showed that our model was able to capture well-established prognostic factors as well as complex and novel patterns to predict patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…We recommend that such trials always involve at least two pathologists for TIL scoring, and rereview by a third pathologist in case of discordance. In addition, the evolving research related to spatial infiltration patterns may impact interpretation of TIL scores in the future [47][48][49] . In our study we did not assess spatial distribution of TILs or interactions with other cells in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…TIME is primarily affected by the interactions between tumor-infiltrating lymphocytes (TILs) and tumor cells. At present, many research fields [ [8] , [9] , [10] , [11] ] have demonstrated that the interaction between TILs and tumor cells is associated with the prognosis of patients. Therefore, it is anticipated that the interactions between TILs and tumor cells will be characterized in order to identify a novel biomarker for prognosis prediction and risk stratification in LUAD.…”
Section: Introductionmentioning
confidence: 99%